Virtual Essay - Moore, Pat (Guará Journal, 2019)
Patricia Frances Moore, or Pat Moore, as she prefers to be called, is English by birth and international by vocation... And she continues to take photographs... She has seen many peoples of the world. And here she presents us with a snapshot of the peoples she has seen.